2012
DOI: 10.1016/j.cub.2012.04.028
|View full text |Cite
|
Sign up to set email alerts
|

Action sounds recalibrate perceived tactile distance

Abstract: The experimental design included three conditions in which the sounds produced by tapping with one's hand on a surface were spatially manipulated. Zero Distance (0D): the tapping sound originated at the tapping location; Double Distance (2D): the sound originated at double the distance to the tapping location; and Quadruple Distance (4D): the sound originated at four times the distance to the tapping location. Participants were instructed to tap at each marked point for ten times, with a frequency of 1 Hz, sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
149
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 125 publications
(159 citation statements)
references
References 10 publications
4
149
0
Order By: Relevance
“…Touch, however, can clearly also be used to perceive the extrinsic physical properties of objects. Longo, Azañón, and Haggard (2010) argued that perceiving the metric properties of objects touching the skin requires that immediate sensory signals be combined with (Berryman, Yau, & Hsiao, 2006), sounds produced by action (Tajadura-Jiménez et al, 2012, 2015, the rubber hand illusion (Bruno & Bertamini, 2010), and tool use (Canzoneri et al, 2013;Miller, Longo, & Saygin, 2014, 2017. Thus, in analogy with the modulation of perceived passability of apertures when apparent eyeheight was altered shown by Warren and Whang (1987), these results show that experimental manipulations of represented body size alter perceived tactile distance.…”
Section: Statement Of Public Significancementioning
confidence: 91%
“…Touch, however, can clearly also be used to perceive the extrinsic physical properties of objects. Longo, Azañón, and Haggard (2010) argued that perceiving the metric properties of objects touching the skin requires that immediate sensory signals be combined with (Berryman, Yau, & Hsiao, 2006), sounds produced by action (Tajadura-Jiménez et al, 2012, 2015, the rubber hand illusion (Bruno & Bertamini, 2010), and tool use (Canzoneri et al, 2013;Miller, Longo, & Saygin, 2014, 2017. Thus, in analogy with the modulation of perceived passability of apertures when apparent eyeheight was altered shown by Warren and Whang (1987), these results show that experimental manipulations of represented body size alter perceived tactile distance.…”
Section: Statement Of Public Significancementioning
confidence: 91%
“…For instance, the sound of tapping with an object on one's hand provides information about hand position, arm length (Tajadura-Jiménez et al, 2012), and force applied (Tajadura-Jiménez, Furfaro, BianchiBerthouze, & Bevilacqua, in press), or the timing of steps when walking (Menzer et al, 2010). Using this information, the individual can adjust movements.…”
Section: Sonification For Representing Understanding and Motivatingmentioning
confidence: 99%
“…Differences in tactile distance perception are often attributed to cortical magnification factors in primary somatosensory cortex (SI) (Cholewiak, 1999;Green, 1982). However, several recent studies have found that tactile distance perception is modulated by altered multisensory input (Miller, Longo, & Saygin, 2014;Tajadura-Jiménez et al, 2012;Taylor-Clarke et al, 2004). Further, quantifications of the magnitude of Weber's illusion (Taylor-Clarke et al, 2004) found it to only be about 10% of what would be expected from cortical magnification factors in SI (Penfield & Boldrey, 1937).…”
Section: Introductionmentioning
confidence: 99%
“…In one popular version of a tactile distance judgment task (TDJ), participants compare the perceived distance of two temporally distinct presentations of touch. Touch is typically administered to two distinct body parts, in order to quantify differences in the represented size of body parts (de Vignemont, Ehrsson, & Haggard, 2005;Tajadura-Jiménez et al, 2012;Taylor-Clarke et al, 2004). It is inferred that the body part with the greatest perceived tactile distance is represented as larger than the other.…”
Section: Introductionmentioning
confidence: 99%